2017
DOI: 10.1149/2.1901713jes
|View full text |Cite
|
Sign up to set email alerts
|

Passivation Behavior and Surface Chemistry of 2507 Super Duplex Stainless Steel in Acidified Artificial Seawater Containing Thiosulfate

Abstract: In this work, passivation behavior and surface chemistry of 2507 super duplex stainless steel (SDSS) in acidified artificial seawater (ASW) containing different concentrations of thiosulfate are investigated using electrochemical techniques, X-ray photoelectron spectroscopy and the Point Defect Model. The 2507 SDSS is resistant to thiosulfate-induced pitting corrosion in the acidified ASW with a] ratio ranging from 59 to 5900, while the film dissolution rate is enhanced, resulting in a higher passive current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 77 publications
4
17
0
Order By: Relevance
“…The use of a CPE instead of an ideal capacitor is owing to the distribution of the relaxation times associated with heterogeneities (including surface defects and roughness) at the surface of the electrodes. 29,33 The Nyquist plots of 304 SS (Figure 6a,b) and Zr 2 N 2 O/SS (Figure 6c,d) display similar trends. At 0.9 V, both samples exhibit a large capacitance.…”
Section: Effect Of Ctps On Impedancementioning
confidence: 73%
“…The use of a CPE instead of an ideal capacitor is owing to the distribution of the relaxation times associated with heterogeneities (including surface defects and roughness) at the surface of the electrodes. 29,33 The Nyquist plots of 304 SS (Figure 6a,b) and Zr 2 N 2 O/SS (Figure 6c,d) display similar trends. At 0.9 V, both samples exhibit a large capacitance.…”
Section: Effect Of Ctps On Impedancementioning
confidence: 73%
“…It can be seen from the positive slope that the passive film on the surface of TA2 exhibits n-type semiconductor characteristics, and the structure of the passive film has oxygen vacancies or metal cation defects [37,38]. The relationship between the space-charge capacitance and applied potential can be expressed by the following equation [37,39]:…”
Section: Electrochemical Characteristicsmentioning
confidence: 99%
“…It means that the higher the seawater depth is, the more defects the film has. Cui et al [25] indicated that the defects had high energy and high activity, which facilitated the anodic dissolution. Consequently, the stability and corrosion resistance of the preformed passive film decrease.…”
Section: Mott-schottky Analysismentioning
confidence: 99%